Análise do efeito de polimorfismos não-sinônimos em genes de reparo de DNA da via BER na resposta inflamatória da meningite - Silva, Thayse Azevedo da (2013)
In vitro and in animal models, APE1, OGG1, and PARP-1 have been proposed as being involved with inflammatory response. In this work, we have investigated if the SNPs APE1 Asn148Glu, OGG1 Ser326Cys, and PARP-1 Val762Ala are associated to meningitis and also developed a system to enable the functional analysis of polymorphic proteins. Patients with bacterial meningitis (BM), aseptic meningitis (AM) and controls (non-infected) genotypes were investigated by PIRA-PCR or PCR-RFLP. DNA damages were detected in genomic DNA by Fpg treatment. IgG and IgA were measured from plasma and the cytokines and chemokines were measured from cerebrospinal fluid samples using Bio-Plex assays. The levels of NF-κB and c-Jun were measured in CSF by dot blot assays. A significant (P<0.05) increase in the frequency of APE1 148Glu allele in BM and AM patients was observed. A significant increase in the genotypes Asn/Asn in control group and Asn/Glu in BM group was also found. For the SNP OGG1 Ser326Cys, the genotype Cys/Cys was more frequent (P<0.05) in BM group. The frequency of PARP-1 Val/Val genotype was higher in control group (P<0.05). The occurrence of combined SNPs increased significantly in BM patients, indicating that these SNPs may be associated to the disease. Increasing in sensitive sites to Fpg was observed in carriers of APE1 148Glu allele or OGG1 326Cys allele, suggesting that SNPs affect DNA repair activity. Alterations in IgG production were observed in the presence of SNPs APE1Asn148Glu, OGG1Ser326Cys or PARP-1Val762Ala. Reductions in the levels ofIL-6, IL-1Ra, MCP-1/CCL2and IL-8/CXCL8 were observed in the presence of APE1148Glu allele in BM patients, however no differences were observed in the levels of NF-κB and c-Jun considering genotypes and analyzed groups. Using APE1 as model, a system to enable the analysis of cellular effects and functional characterization of polymorphic proteins was developed using strategies of cloning APE1 cDNA in pIRES2-EGFP vector, cellular transfection of the construction obtained, siRNA for endogenous APE1 and cellular cultures genotyping. In conclusion, we obtained evidences of an effect of SNPs in DNA repair genes on the regulation of immune response. This is a pioneering work in the field that shows association of BER variant enzymes with an infectious disease in human patients, suggesting that the SNPs analyzed may affect immune response and damage by oxidative stress level during brain infection. Considering these data, new approaches of functional characterization must be developed to better analysis and interactions of polymorphic proteins in response to this context